Synthesis, Crystal Structure and Fluorescence Property of Iron(II) Complex [Fe(phen)3](pydc)·9H2O - Chen, Shu-Yang; Sun, Hong-Xian; Guo, Ying-Chen; Cao, Feng-Pu (Asian Journal of Chemistry, 2013)
A new iron(II) complex, [Fe(phen)3](pydc)·9H2O, has been synthesized by the reaction of ferrous sulfate, 2,6-pyridine dicarboxylic acid (pydcH2) and 1,10-phenanthroline (phen) and characterized by elemental analysis, IR, TG and X-ray single-crystal diffraction. It crystallizes in monoclinic, space group C/2c, with a = 28.477(8), b = 19.042(5), c = 20.861(8) Å, b = 129.52(2), V = 8726(5) Å3, C43H45FeN7O13, Mr = 923.57, Z = 8, Dc = 1.379 Mg/m3, l(MoKa) = 0.71073 Å, μ = 0.418 mm-1, F(000) = 3712, S = 1.062, the final R = 0.0624 and wR = 0.2083 for 5540 observed reflections (I > 2s(I)). The Fe(II) is coordinated with six nitrogen atoms from three 1,10-phenanthroline molecules making a distorted octahedron [Fe(phen)3]2+ and a pydc2- as a counter anion. A two-dimensional layer structure is constructed by the interactions between [Fe(phen)3]2+ and pydc2-. Fluorescence spectral analysis shows that the complex has a fluorescence-emission at around 360 nm (CCDC:822144).